Isolation and identification of a bacterial strain from Pharmaceutical Industrial Wastewater and Sludge - Bojja, Lavanya; Vadluri, Rajendar (Journal of Neonatal Surgery, 2025)
Pharmaceutical industrial wastewater and sludge represent significant environmental pollutants, containing persistent organic compounds that challenge conventional treatment methods. This study aimed to isolate and identify an efficient bacterial strain capable of biodegradation from pharmaceutical industrial effluents. Using serial dilution and nutrient agar culturing techniques, bacterial strain LSR-3 was successfully isolated. Morphological analysis revealed that LSR-3 is Gram-positive with round, convex colonies producing a yellow pigment. Further molecular identification through 16S-rDNA sequencing showed 98% similarity to Brevibacillus agri. Phylogenetic analysis confirmed its close evolutionary relationship to other Brevibacillus strains, particularly strain DSM 6348. Biodegradation assays demonstrated that Brevibacillus agri LSR-3 achieved the highest reduction in Chemical Oxygen Demand (COD) among tested strains, with peak reductions of 52% for pharmaceutical industrial wastewater (PIW) and 48% for Diclofenac (DCF) within 36–48 hours of incubation. Optimal COD reductions were recorded at 45% for 10% PIW concentration and 32% for 100 mg/L DCF concentration. These results indicate the strain’s metabolic versatility and adaptability under polluted conditions. The findings underscore the potential of Brevibacillus agri LSR-3 as a strong candidate for bioremediation applications in industrial wastewater treatment, offering a sustainable, eco-friendly approach to mitigating pharmaceutical pollutants. Further studies are suggested to optimize operational conditions to maximize degradation efficiencies for large-scale applications.